2001
DOI: 10.1086/322616
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficileInfection in Patients with Neutropenia

Abstract: Clostridium difficile is the most important cause of nosocomial infectious diarrhea. The importance of C. difficile-associated diarrhea (CDAD) has been poorly investigated in patients with neutropenia who have hematologic malignancies. A retrospective chart review of all patients treated in the leukemia ward of a university medical center during 1991-2000 determined that 875 courses of myelosuppressive chemotherapy were administered. CDAD occurred in 7.0% of all cycles. In 8.2% of the patients, severe enteroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
5
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 25 publications
8
94
5
3
Order By: Relevance
“…The authors found that CDAD was the second most common infectious complication occurring in this cohort. Gorschlu¨ter et al 26 analyzed their data on 875 courses of myelosuppressive therapy in 371 patients with hematologic malignancies and reported a 7% incidence of CDAD (61 episodes in 53 patients). Diarrhea was defined as at least two loose stools per day.…”
Section: Cdad In Hsct Recipientsmentioning
confidence: 99%
“…The authors found that CDAD was the second most common infectious complication occurring in this cohort. Gorschlu¨ter et al 26 analyzed their data on 875 courses of myelosuppressive therapy in 371 patients with hematologic malignancies and reported a 7% incidence of CDAD (61 episodes in 53 patients). Diarrhea was defined as at least two loose stools per day.…”
Section: Cdad In Hsct Recipientsmentioning
confidence: 99%
“…However, studies of CDAD in hematopoietic cell transplantation patients disagree about the incidence of, severity of, and risk factors for CDAD. [2][3][4][5][6][7][8][9][10] A lack of differentiation between mild cases and severe cases of CDAD may explain some of these discrepancies. To address this deficiency and to further study CDAD outcomes among allogeneic stem cell transplant recipients, we developed and validated a grading system for CDAD severity using a modified version of the National Cancer Institute Common Terminology Criteria for Adverse Events, version 3.0 (CTCAE) and based on the presenting clinical CDAD symptoms.…”
Section: Infect Control Hosp Epidemiol 2007; 28:208-211mentioning
confidence: 99%
“…A study found that gastrointestinal colonization with toxigenic Clostridium difficile occurred in 12% of recipients of HPC transplant on admission to the hospital [6]. In addition, these patients are immunocompromised, receive extensive exposure to broad spectrum antimicrobials before and after HPC transplant, have compromise of the integrity of the intestinal mucosa due to the high dose chemoradiation given to the patients as part of transplant preparative regimens, and also often have very prolonged hospital stay [7][8][9]. Studies have shown the association of CDI with the development of acute Graft-versus-host disease (GVHD) [10,11] and increased non-relapse mortality [10] after allogeneic HPC transplant.…”
Section: Introductionmentioning
confidence: 99%